Modulation of p53 activity in the pregnant mouse. (16th November 2010) - Sharp, A; Cardenas, I; Heazell, AEP; Baker, PN; Crocker, IP; Mor, G
Abstract : The pregnancy complications pre-eclampsia and Intrauterine growth restriction are associated with increased trophoblast apoptosis and expression of the cell cycle regulator p53. Previously the authors have demonstrated that activation of p53 with the specific Mdm2 inhibitor, Nutlin, induces apoptosis in trophoblast cell lines. Our objective was to determine whether Nutlin affects pregnancy outcome in vivo. Female C57Bl6 mice received an intraperitoneal injection of 20 mg/kg Nutlin or vehicle control 8.5 days postconception (dpc). This treatment was repeated every 48 h for a total of five treatments. Serum was collected and organs harvested at 17.5 dpc. Treatment with Nutlin had no effect on pregnancy outcome. Nutlin treated animals showed increased serum M30 activity, representing cleavage of cytokeratin 18 (p<0.05, Mann–Whitney). Caspase-3/7 was increased in the decidua (p<0.05, Mann–Whitney), but not in the placenta. Expression of p53 was not altered in placenta or decidua, but expression of the p53 target Mdm2 was increased in decidua samples. There was no effect upon p53 or Mdm2 expression in the placenta. The increased caspase activity and Mdm2 expression in the decidua suggests good drug penetrance of maternal tissues by Nutlin. The lack of apoptosis or protein activation within the placenta implies either impairment of drug transfer or innate resistance of the placenta to p53 activation with Nutlin. In summary, Nutlin is able to induce p53 mediated effects within pregnant mice; however the placenta and fetus appear to be protected.